(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Language contact, the interaction between speakers of different languages, has long been recognized as a catalyst for linguistic change, particularly in phonological systems. This research paper examines how language contact influences phonological systems through processes such as borrowing, convergence, and diffusion.